Implementation of Social Capital in Community Empowerment (Case Study in Komunitas Ketimbang Ngemis Bandung) - Falah, Afiatun Nur (International Journal Pedagogy of Social Studies, 2022)
This research focused on implementation in community empowerment efforts by social capital. Social capital developed in the community can be the sustainable and empowerment reinforcement of the community in the society. The purpose of this study is to describe the efforts to empower the KNB community, to describe the social capital implementation in empowering the KNB community, and to analyze the social capital in the KNB community that can be implemented in the social studies learning process. The approach used a qualitative approach and case studies with data collection methods using observation, interviews, and documentary studies. The findings indicated that empowerment has done by the KNB community includes the awareness stage, the capacity building stage, the empowerment stage, and the evaluation stage. Meanwhile, social capital has implemented in norms, beliefs, and networks. There are two norms in the KNB community, which are written and verbal forms. Trust in the KNB community can be seen internally through the division of work and management, and externally through the value of honesty application in building cooperation with donors. The network formed results from social relations that exist with the company or the community. In the field of education, social capital can be implemented in the social studies learning process through the internalization of social capital studies in social studies material and strengthening social capital for the character of students.